Proceedings 30th IEEE International Symposium on Multiple-Valued Logic (ISMVL 2000)
DOI: 10.1109/ismvl.2000.848599
|View full text |Cite
|
Sign up to set email alerts
|

Fast transforms for multiple-valued input binary output PLI logic

Abstract: Fast forward and inverse transforms for multiplevalued input binary output PLI logic are derived. New matrix functions are introduced which allow feasible tranformation of arbitrary q-valued input binary output functions. This allows representation of the function in the algebra of GF(2), where q m 2 . The representation of MVB functions in various functional bases having always fast algorithms is the foundation for the efficient synthesis of PLI expansions of MVB functions. The computational complexity of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Generalization of LI transforms for multiple-valued input binary functions was proposed in [6]. Properties of LI transformation matrices and their complexity analysis for multiple-valued input binary output functions with appropriate coding and new matrix functions were discussed in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Generalization of LI transforms for multiple-valued input binary functions was proposed in [6]. Properties of LI transformation matrices and their complexity analysis for multiple-valued input binary output functions with appropriate coding and new matrix functions were discussed in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Further research showed that there are some LI transforms having the smallest computational cost that is lower than that of the binary Reed-Muller transform [11]. Generalization of LI transforms for multiple-valued input binary functions was proposed in [8] and some efficient class of such transformations was identified in [4]. Binary fixed polarity Reed-Muller expansions have been extended to ternary field GF (3) and in general to a prime field GF(p) [2,5,7].…”
Section: Introductionmentioning
confidence: 99%